Assessing the coffee canopy light absortion based on the leaf area - Pilau, Felipe Gustavo; Angelocci, Luiz Roberto (Coffee Science - ISSN 1984-3909, 2016)
The study evaluated solar radiation interception patterns (K*) defining the relations of interception efficiency (εint) and extinction coefficient (k) of coffee trees (cv. Obatã IAC 1669-20) under leaf area changes. Aiming to determine these interactions for coffee plants (3 years old) under manual defoliations, solar radiation transmitted was measured with two tube solarimeters placed at ground level below the crowns. A canopy-light interception model was derived using the extinction coefficient approach (Monsi & Saeki theory) to assess with independent data to estimate K*. Under absence of leaves, an intense interference of leaves supporting structures over εint was observed, with a minimum value of 0.34. The results were also distinct for obtaining k. The derived model well simulated the K* against measurements, with Willmott index as high as 0.92, improving modeling accuracy using ‘k’ from quadratic fit.